Fusion and the cosmos - H.Wilhelmsson (Condensed Matter Physics, 2004)
In the following investigation we pay special attention to the role of self-organization in fusion plasma physics and in the cosmos. We present a new approach to the expansion of the universe. Formally the technique developed relies on our experience from treating hot fusion plasmas. We account for the possibility that the universe, as it seems, could have a finite life-time (even if it is counted in billions of years), and combine this assumption with the experimental observation that the velocity of separation of distant galaxies is proportional to the distance between the galaxies (the Hubble law). By analysis of a NL PDE (nonlinear partial differential equation) we succed in proving that the crucial value of an exponent has a simple linear relationship with the Hubble constant. It is recognized that the scale-length that we use as a measure of the expansion is equivalent to the Einstein radius of curvature. The final results suggest that the Hubble law should be extended by a factor, which could have an explosive tendency of growth in time (open universe), or a decaying character (closed universe). The possibility of reversed expansion or an oscillating universe "cosmic pendulum" is also discussed.